2012
DOI: 10.1096/fj.12-215228
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of systemic markers of inflammation in atomic‐bomb survivors with special reference to radiation and age effects

Abstract: Past exposure to atomic bomb (A-bomb) radiation has exerted various long-lasting deleterious effects on the health of survivors. Some of these effects are seen even after >60 yr. In this study, we evaluated the subclinical inflammatory status of 442 A-bomb survivors, in terms of 8 inflammation-related cytokines or markers, comprised of plasma levels of reactive oxygen species (ROS), interleukin (IL)-6, tumor necrosis factor α (TNF-α), C-reactive protein (CRP), IL-4, IL-10, and immunoglobulins, and erythrocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…Apart from the induction of adhesion molecules, the levels of cytokines such as interleukin (IL)-6 and IL-8, and other inflammatory molecules, such as transforming growth factor-β (TGF-β), were shown to increase after high and moderate irradiation (93,94). In addition, the Japanese atomic bomb survivors' cohort showed signs of a general increased state of inflammation, with increased levels of IL-6 and C-reactive protein (CRP) (95). In addition to pro-inflammatory responses, there is evidence of pro-thrombotic changes after irradiation of the endothelium.…”
Section: Molecular and Cellular Mechanisms Underlying The Observedmentioning
confidence: 99%
“…Apart from the induction of adhesion molecules, the levels of cytokines such as interleukin (IL)-6 and IL-8, and other inflammatory molecules, such as transforming growth factor-β (TGF-β), were shown to increase after high and moderate irradiation (93,94). In addition, the Japanese atomic bomb survivors' cohort showed signs of a general increased state of inflammation, with increased levels of IL-6 and C-reactive protein (CRP) (95). In addition to pro-inflammatory responses, there is evidence of pro-thrombotic changes after irradiation of the endothelium.…”
Section: Molecular and Cellular Mechanisms Underlying The Observedmentioning
confidence: 99%
“…One of its three main scientific questions deals with non- 49 cancer effects, such as CVD or cataracts at doses below 0.5 Gy. 50 Currently, the evidence from epidemiological studies for a causal 51 relationship between ionising radiation and CVD risk at doses 52 below 0.5 Gy is weak and the underlying biological mechanisms 53 not understood [20] -indeed they are not delineated even at 54 higher doses, although plausible inflammatory explanations have 55 been hypothesised [2]. An increased risk at low ionising radiation 56 doses would have major implications for radiation protection of 57 the public, radiation-exposed workers and patients.…”
Section: Q2mentioning
confidence: 99%
“…Cohort failure mortality [51], and in long-term levels of inflammatory 149 markers [52][53][54] have also been found among atomic-bomb 150…”
Section: Studymentioning
confidence: 99%
“…Some suggested that the health risks of doses of less than 10 cGy cannot be measured, while others claimed that no dose of ionizing radiation can be considered completely safe and that the use of radiation must always be determined on the basis of risk versus benefit [12–15]. However, the former idea ignores the effect of interaction between radiation-induced stress and other stress conditions that may enhance diseases and the risk of oxidative stress-induced cancer, particularly in ageing patients [5,6,1618]. …”
Section: Introductionmentioning
confidence: 99%
“…The evidence suggests a strong association between cardiovascular disease, ageing and exposure to low-to-moderate levels of radiation [5,6]. Other clinically important consequences of exposure to radiation are retina degeneration and eye cataracts, which were previously thought to be deterministic or tissue reactions but are currently recognized as possibly stochastic in nature and determined by much lower radiation levels than previously believed [3335].…”
Section: Introductionmentioning
confidence: 99%